Shock-Induced Endothelial Dysfunction is Present in Patients With Occult Hypoperfusion After Trauma. Issue 1 (January 2022) - Kregel, Heather R.; Hatton, Gabrielle E.; Isbell, Kayla D.; Henriksen, Hanne H.; Stensballe, Jakob; Johansson, Per I.; Kao, Lillian S.; Wade, Charles E.
ABSTRACT: Background: Shock-induced endothelial dysfunction, evidenced by elevated soluble thrombomodulin (sTM) and syndecan-1 (Syn-1), is associated with poor outcomes after trauma. The association of endothelial dysfunction and overt shock has been demonstrated; it is unknown if hypoperfusion in the setting of normal vital signs (occult hypoperfusion [OH]) is associated with endothelial dysfunction. We hypothesized that sTM and Syn-1 would be elevated in patients with OH when compared to patients with normal perfusion. Methods: A single-center study of patients requiring highest-level trauma activation (2012–2016) was performed. Trauma bay arrival plasma Syn-1 and sTM were measured by enzyme-linked immunosorbent assay. Shock was defined as systolic blood pressure (SBP) <90 mm Hg or heart rate (HR) ≥120 bpm. OH was defined as SBP ≥ 90, HR < 120, and base excess (BE) ⩽−3. Normal perfusion was assigned to all others. Univariate and multivariable analyses were performed. Results: Of 520 patients, 35% presented with OH and 26% with shock. Demographics were similar between groups. Patients with normal perfusion had the lowest Syn-1 and sTM, while patients with OH and shock had elevated levels. OH was associated with increased sTM by 0.97 ng/mL (95% CI 0.39–1.57, p  = 0.001) and Syn-1 by 14.3 ng/mL (95% CI −1.5 to 30.2, p  = 0.08). Furthermore, shock was associated with increased sTM by 0.64 (95% CI 0.02–1.30, p  = 0.04) and with increased Syn-1 by 23.6 ng/mL (95% CI 6.2–41.1, p  = 0.008). Conclusions: Arrival OH was associated with elevated sTM and Syn-1, indicating endothelial dysfunction. Treatments aiming to stabilize the endothelium may be beneficial for injured patients with evidence of hypoperfusion, regardless of vital signs.